Imaging activity in astrocytes and neurons with genetically encoded calcium indicators following in utero electroporation - Gee, J. Michael; Gibbons, Meredith B.; Taheri, Marsa; Palumbos, Sierra; Morris, S. Craig; Smeal, Roy M.; Flynn, Katherine F.; Economo, Michael N.; Cizek, Christian G.; Capecchi, Mario R.; Tvrdik, Petr; Wilcox, Karen S.; et al. (Frontiers in Molecular Neuroscience, 2015)
Complex interactions between networks of astrocytes and neurons are beginning to be appreciated, but remain poorly understood. Transgenic mice expressing fluorescent protein reporters of cellular activity, such as the GCaMP family of genetically encoded calcium indicators (GECIs), have been used to explore network behavior. However, in some cases, it may be desirable to use long-established rat models that closely mimic particular aspects of human conditions such as Parkinson's disease and the development of epilepsy following status epilepticus. Methods for expressing reporter proteins in the rat brain are relatively limited. Transgenic rat technologies exist but are fairly immature. Viral-mediated expression is robust but unstable, requires invasive injections, and only works well for fairly small genes (<5 kb). In utero electroporation (IUE) offers a valuable alternative. IUE is a proven method for transfecting populations of astrocytes and neurons in the rat brain without the strict limitations on transgene size. We built a toolset of IUE plasmids carrying GCaMP variants 3, 6s, or 6f driven by CAG and targeted to the cytosol or the plasma membrane. Because low baseline fluorescence of GCaMP can hinder identification of transfected cells, we included the option of co-expressing a cytosolic tdTomato protein. A binary system consisting of a plasmid carrying a piggyBac inverted terminal repeat (ITR)-flanked CAG-GCaMP-IRES-tdTomato cassette and a separate plasmid encoding for expression of piggyBac transposase was employed to stably express GCaMP and tdTomato. The plasmids were co-electroporated on embryonic days 13.5–14.5 and astrocytic and neuronal activity was subsequently imaged in acute or cultured brain slices prepared from the cortex or hippocampus. Large spontaneous transients were detected in slices obtained from rats of varying ages up to 127 days. In this report, we demonstrate the utility of this toolset for interrogating astrocytic and neuronal activity in the rat brain.